Features of the Stressed-Strain State of a Steel-Reinforced-Concrete Span Structure with Preliminary Bending of a Steel Beam - Popovych, M. M; Kliuchnyk, S. V (Science and Transport Progress, 2022)
Purpose. The authors aim to determine the features of the operation of a steel-reinforced concrete span structure with beams reinforced with an I-beam, with their pre-stressing using the bending of a steel I-beam. Methodology. To manufacture a steel-reinforced concrete span structure, it was proposed to reinforce an I-beam with a camber, which is then leveled with the help of applied external loads. For practical convenience, the vertical external forces are replaced by horizontal forces that keep the metal I-beam in a deformed state and in this state it is concreted. After the concrete strength development, the external forces are removed and the metal I-beam creates the pre-stressing of the concrete. Findings. When determining stresses, checking calculations by analytical method and the method of modeling with the help of the ANSYS program were used. The stress diagrams along the lower and upper fibers of a metal I-beam and stresses in concrete in the upper and lower zones of the beam were constructed. The analysis of the results showed that the pre-bending of a metal beam can be used to create a pre-stressing, which improves the performance of steel-reinforced concrete span structures, increases their rigidity and allows using of such a structure to increase the balks of railway and highway bridges. Originality. In the paper, a study of the stress-strain state of steel-reinforced concrete beams of the railway span structure was carried out, taking into account the pre-stressing of the concrete. A method of manufacturing a steel-reinforced concrete beams is proposed, which provides pre-stressing of the reinforced concrete due to the bending of a steel I-beam. Practical value. As a result of the calculations, it was found that the structure, when manufactured by the specified method, has greater rigidity compared to reinforced concrete or metal beams. The height of the beam can be lower compared to reinforced concrete or metal span structures. These circumstances are essential for railway bridges, especially for high-speed traffic ones.